Attention‐deficit hyperactivity disorder, multimodal treatment, and longitudinal outcome: evidence, paradox, and challenge. Issue 1 (3rd November 2014) - Hinshaw, Stephen P.; Arnold, L. Eugene; ,
Abstract : Given major increases in the diagnosis of attention‐deficit hyperactivity disorder (ADHD) and in rates of medication for this condition, we carefully examine evidence for effects of single versus multimodal (i.e., combined medication and psychosocial/behavioral) interventions for ADHD. Our primary data source is the Multimodal Treatment Study of Children with ADHD (MTA), a 14‐month, randomized clinical trial in which intensive behavioral, medication, and multimodal treatment arms were contrasted with one another and with community intervention (treatment‐as‐usual), regarding outcome domains of ADHD symptoms, comorbidities, and core functional impairments. Although initial reports emphasized the superiority of well‐monitored medication for symptomatic improvement, reanalyses and reappraisals have highlighted (1) the superiority of combination treatment for composite outcomes and for domains of functional impairment (e.g., academic achievement, social skills, parenting practices); (2) the importance of considering moderator and mediator processes underlying differential patterns of outcome, including comorbid subgroups and improvements in family discipline style during the intervention period; (3) the emergence of side effects (e.g., mild growth suppression) in youth treated with long‐term medication; and (4) the diminution of medication's initial superiority once the randomly assigned treatment phase turned into naturalistic follow‐up. The key paradox is that while ADHD clearly responds to medication and behavioral treatment in the short term, evidence for long‐term effectiveness remains elusive. We close with discussion of future directions and a call for greater understanding of relevant developmental processes in the attempt to promote optimal, generalized, and lasting treatments for this important and impairing neurodevelopmental disorder. WIREs Cogn Sci 2015, 6:39–52. doi: 10.1002/wcs.1324 This article is categorized under: Psychology > Attention